Co-Production Process of Kampung Warna-Warni: Societal Active Participatory in the Urban Slum Management - Alfian, Faqih; Ruriana, Alvinda Putri; Ayu, Galuh Anissa Sekar; Adiputra, Bayu Galen; Marpaung, Nethaneel Yobel; Alwan, Ken Arya Fauzan (UI Scholars Hub, 2024)
This research analyses the Co-production process in developing Kampung Warna-Warni Jodipan, Malang City, and its implications for city government regulations regarding urban slum areas. The author uses descriptive qualitative data to explore the co-production process based on primary data obtained through semi-structured interviews with residents of Kampung Warna-Warni and the local Malang city government. Research findings show that the active participation of the community, students, private sponsors, and government agents can create a balance between community autonomy and the need for supervision and assistance from the government, as well as strengthening the bargaining position of the residents of Kampung Warna-Warni. Furthermore, the Kampung Warna-Warni improvement program has become a pilot model used by the Malang City government to regulate other slum settlements. The context of this research is limited to the case of Kampung Warna-Warni Malang City, which succeeded in getting recognition from the government, so the stages of the Co-production process will differ from the case of slum settlements, which the government does not recognise. Future researchers can explore this matter to find comparative patterns of co-production development in recognized and non-recognized slum settlements.